Occurrence of regulated mycotoxins and other microbial metabolites in dried cassava products from Nigeria - Abass, A.; Awoyale, W.; Sulyok, M.; Alamu, Emmanuel Oladeji (MDPI, 2017)
Dried cassava products are perceived as one of the potential sources of mycotoxin ingestion in human foods. Processing either contributes to the reduction of toxins or further exposes products to contamination by microorganisms that release metabolic toxins into the products. Thus, the prevalence of microbial metabolites in 373 processed cassava products was investigated in Nigeria. With the use of liquid chromatography tandem-mass spectrometry (LC-MS/MS) for the constituent analysis, a few major mycotoxins (aflatoxin B1 and G1, fumonisin B1 and B2, and zearalenone) regulated in food crops by the Commission of the European Union were found at concentrations which are toxicologically acceptable in many other crops. Some bioactive compounds were detected at low concentrations in the cassava products. Therefore, the exposure of cassava consumers in Nigeria to regulated mycotoxins was estimated to be minimal. The results provide useful information regarding the probable safety of cassava products in Nigeria